Intense Focused Ultrasound Preferentially Stimulates Subcutaneous and Focal Neuropathic Tissue: Preliminary Results. Issue 1 (8th November 2012) - McClintic, Abbi M.; Dickey, Trevor C.; Gofeld, Michael; Kliot, Michel; Loeser, John D.; Richebe, Philippe; Mourad, Pierre D.
Abstract Objective. Potential peripheral sources of pain from subcutaneous tissue can require invasive evocative tests for their localization and assessment. Here, we describe studies whose ultimate goal is development of a noninvasive evocative test for subcutaneous, painful tissue. Design. We used a rat model of a focal and subcutaneous neuroma to test the hypothesis that intense focused ultrasound can differentiate focal and subcutaneous neuropathic tissue from control tissue. To do so, we first applied intense focused ultrasound (2 MHz, with individual pulses of 0.1 second in duration) to the rat's neuroma while the rat was under light anesthesia. We started with low values of intensity, which we increased until intense focused ultrasound stimulation caused the rat to reliably flick its paw. We then applied that same intense focused ultrasound protocol to control tissue away from the neuroma and assayed for the rat's response to that stimulation. Results. Intense focused ultrasound of sufficient strength (ISATA of 600 +/− 160 W/cm2) applied to the neuroma caused the rat to flick its paw, while the same intense focused ultrasound applied millimeters to a centimeter away failed to induce a paw flick. Conclusion. Successful stimulation of the neuroma by intense focused ultrasound required colocalization of the neuroma and intense focused ultrasound supporting our hypothesis.